2017
DOI: 10.1021/acscatal.6b03440
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Channeling in an Artificial Metabolon: A Molecular Dynamics Blueprint for an Experimental Peptide Bridge

Abstract: Natural enzyme cascades utilize electrostatic guidance as an effective technique to control the diffusion of charged reaction intermediates between catalytic active sites in a process known as substrate channeling. However, the limited understanding of channeling mechanisms has abated the application of this technique in artificial catalytic cascades. In this work, we utilize molecular dynamics simulations to describe the transport of anionic intermediates (e.g., oxalate and glucose-6-phosphate) on a theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 27 publications
2
75
0
Order By: Relevance
“…We attributed the threefold kinetic enhancement to the closer spatial and diffusive coupling of the cascade reaction at the HRP‐containing membrane such that H 2 O 2 and ABTS were more effectively channeled between the two enzymes in the early stages of the reaction. In contrast, the reaction rates became comparable at later time stages (Figure m) as diffusive mixing became predominant, in agreement with previous studies on enzyme channelling …”
Section: Figuresupporting
confidence: 92%
“…We attributed the threefold kinetic enhancement to the closer spatial and diffusive coupling of the cascade reaction at the HRP‐containing membrane such that H 2 O 2 and ABTS were more effectively channeled between the two enzymes in the early stages of the reaction. In contrast, the reaction rates became comparable at later time stages (Figure m) as diffusive mixing became predominant, in agreement with previous studies on enzyme channelling …”
Section: Figuresupporting
confidence: 92%
“…A major advantage of this approach is that the scaffold architecture, and therefore, the enzyme stoichiometric ratios can be easily controlled in a modular fashion (Pröschel et al ). In a recent example, artificial peptide scaffolded, synthetic metabolons of hexokinase (HXK) and glucose‐6‐phosphate dehydrogenase (G6PDH), were proven to be more efficient than the free enzymes for metabolic engineering (Liu et al ). Such studies suggest that synthetically varying the proportion of TCA cycle enzymes that are complexed, as opposed to unbound, likely represents an interesting strategy for future studies.…”
Section: Perspectives For Synthetic Biology Approaches At Modifying Tmentioning
confidence: 99%
“…The authors found that this was due to increased enzyme stability and a local environment affect (due to DNA surface affinity or a hydration layer) and not substrate channeling [47]. Another illustrative example is by Liu et al, who used a predominantly-lysine cationic bridge between two coupled enzymes (hexokinase and glucose-6-phosphate dehydrogenase) to facilitate substrate channeling of the dual-negatively charged intermediate [75]. A similarly-long neutral bridge did not show evidence of substrate channeling.…”
Section: Factors Affecting Immobilization Benefits-immobilization Chementioning
confidence: 99%